Quantitative Analysis of Self-Potential Anomaly: Derivative Analysis, Least-Squares Method and Non-Linear Inversion - Wahyu Srigutomo; Eleonora Agustine; M. Habri Zen (Indonesian Journal of Physics, 2006)
Despite the broadly usage in geophysical fields due to its non-intrusiveness, inexpensiveness and fast deployment, self-potential (SP) method still posses challenges in the interpretation. In this work, quantitative identification of SP parameters such as the shape factor of cylindrical and spherical objects, the depth of burial, the polarization angle and the electric dipole moment is addressed. Three approaches of quantitative interpretation are used, i.e., a derivative method, a least-squares method and an iterative inversion based on the Levenberg-Marquardt method. The above approaches were first tested on a theoretical synthetic model, where a close agreement between the presumed and calculated parameters was obtained. Application to the real data was conducted by analyzing the SP anomaly obtained from a buried cylindrical conductive object at certain depth.